Novel high-performance and cost-effective green inhibitor based on fundamental theoretical evaluations combined with electrochemical/surface examinations of Arachis hypogaea shell extract for pipeline steel corrosion in 1 M H2SO4 solution - Alice Osheiza Alao; Abimbola Patricia Popoola; Omotayo Sanni; Modupeola Dada (Materials Research Express, 2024)
Traditional corrosion inhibitors have been frequently used for metal protection against strong acids. However, most of them are hazardous compounds with high costs. Therefore, due to the strict environmentally friendly regulations, green and low-cost compounds from renewable sources have gained high consideration in recent applications. In the present study, the Arachis hypogaea shell extract, commonly called groundnut, a cost-effective was selected to inhibit API X 65 pipeline steel corrosion in 1 mol·L ^−1 H _2 SO _4 solution. The Arachis hypogaea shell composition was examined by FTIR analysis. The Arachis hypogaea shell on pipeline steel in H _2 SO _4 solutions was studied via gravimetric, potentiodynamic polarization, and surface analysis (SEM and EDX). Electron donor atoms present in the Arachis hypogaea shell extract molecules is responsible for its adsorption on the surface of the metal. Experimental study shows that with increasing Arachis hypogaea shell concentrations, the inhibition tendency increased and reached 98.84% at 4 g L ^−1 after 24 h. Arachis hypogaea shell extract behaved as mixed-type inhibitor, and the surface coverage fits the Langmuir isotherm, signifying that the steel surface was covered by a monolayer of inhibitor molecules without intermolecular interactions. SEM analysis shows that Arachis hypogaea molecule adsorption on the metal surface reduced considerably its dissolution rate resulting in a smooth and clean surface with few damaged areas. The use of water for extraction of Arachis hypogaea shell exhibiting inhibition efficiency, non-toxic, and cost-effective than other green inhibitors, proposes the Arachis hypogaea shell as an excellent green inhibitor for API X 65 steel corrosion in 1 mol·L ^−1 H _2 SO _4 solution.